2022
DOI: 10.3390/su14138039
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Identification and Sliding Pressure Control of a Supercritical Power Plant Using Whale Optimizer

Abstract: Sliding pressure control is a well-known method of controlling supercritical power plants that improves energy efficiency and reduces pressure dynamic stresses. This paper presents a novel approach for developing a supercritical cleaner coal power plant’s sliding pressure control strategy. First, using Whale Optimizer, a nonlinear identified transfer matrix model was created (WO). By comparing simulations and errors, the WO clearly outperforms the GA and Grey-Wolf Optimizer (GWO) techniques on parameter identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The battery's thermal mass is represented by 𝑀 𝑡ℎ , T is the battery temperature, 𝑉 𝑇,𝑖 is the voltage drop across the resistor 𝑅 𝑇,𝑖 . The Whale Optimizer previously showed its intelligence algorithm in optimizing and identifying the unknown parameters is used in this research to estimate model parameters by optimization of the HPPC test results at each SoC level separately for more accurate estimation [26]. However, these parameters are functions of temperature, SoC, and aging.…”
Section: ) Hppc Testmentioning
confidence: 99%
“…The battery's thermal mass is represented by 𝑀 𝑡ℎ , T is the battery temperature, 𝑉 𝑇,𝑖 is the voltage drop across the resistor 𝑅 𝑇,𝑖 . The Whale Optimizer previously showed its intelligence algorithm in optimizing and identifying the unknown parameters is used in this research to estimate model parameters by optimization of the HPPC test results at each SoC level separately for more accurate estimation [26]. However, these parameters are functions of temperature, SoC, and aging.…”
Section: ) Hppc Testmentioning
confidence: 99%
“…6 The data signals have been extensively used in many different research applications concerning modeling and control. 6,11,14 The data can be used throughout lifespan of supercritical units and has no expiry date as long as this type of plants is still in operation. This is because they are subject to regular maintenance that avoids deterioration in equipment and/or dynamic performance and it is then confirmed that no significant change has occurred on the data in this period.…”
Section: Model Identification and Verificationmentioning
confidence: 99%
“…In control theory, the controlled reference correction, by predictive control or intelligent inverse control, is capable of increasing the speed of the response of the various actuators in the regulatory layer of control. 7,13,14,46 The load signal taken from set of data portion representing the once-through operation has been injected as an expected demand signal in order to observe the effect of the upgraded controller on the inputs, especially the coal consumption. As depicted in Figures 24 and 25, which represents the power output and coal flow input, respectively, the load demand is followed smoothly by the inverse controller, and that is also reflected in the coal consumption that has been robustly smoothed and minimized.…”
Section: Simulation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…From a deep investigation of the literature, Whale Optimizer (WO) is still not applied and evaluated in the field of gas turbines' modeling and control. Although WO has been applied for a coal unit [22], it is worth investigating specifically on GT control system because of the high number of differences in the design, characteristics, and practical viability between the two types of power plants, which offers an opportunity for more novel achievements in this research area. The contributions of this paper are then stated as follows:…”
mentioning
confidence: 99%